Search for top squarks decaying via four-body or chargino-mediated modes in single-lepton final states in proton-proton collisions at root s=13 TeV - Yetkin, Elif Aslı (SPRINGER, 2018)
A search for the pair production of the lightest supersymmetric partner of the top quark ((t) over tilde (1)) is presented. The search focuses on a compressed scenario where the mass difference between the top squark and the lightest supersymmetric particle, often considered to be the lightest neutralino (( chi) over tilde (0)(1)), is smaller than the mass of the W boson. The proton-proton collision data were recorded by the CMS experiment at a centre-of-mass energy of 13 TeV, and correspond to an integrated luminosity of 35.9 fb(-1). In this search, two decay modes of the top squark are considered: a four-body decay into a bottom quark, two additional fermions, and a (chi) over tilde (1)(0); and a decay via an intermediate chargino. Events are selected using the presence of a high-momentum jet, significant missing transverse momentum, and a low transverse momentum electron or muon. Two analysis techniques are used, targeting different decay modes ((t) over tilde (1)): of the a sequential selection and a multivariate technique. No evidence for the production of top squarks is found, and mass limits at 95% confidence level are set that reach up to 560 GeV, depending on the m((t) over tilde (1)) - m((chi) over tilde (0)(1)) mass difference and the decay mode.
Keywords: Hadron-Hadron scattering (experiments); Supersymmetry